Project management and quality decision-making towards improved life-cycle infrastructure design and construction in rough terrain and inclement environments - Malik, Shariful Alam (Curtin University, 2015)
Infrastructure development is time consuming and involving perpetual investment, especially for highways in rugged terrains. The major objective of this study was to identify the scheduling, risk variables, contractual and environmental variables involved in quality management decision making for projects in inclement conditions, and examine their respective impacts. Two projects, one in Bangladesh and also in Afghanistan were examined towards development of a guideline and recommendation for improved stakeholder decisionmaking for infrastructure design and construction.